Interactive effects of digestible protein levels on thermal and physical stress responses in Nile tilapia - Freitas, Jakeline Marcela Azambuja de [UNESP]; Peres, Helena; Carvalho, Pedro Luiz Pucci Figueiredo de [UNESP]; Furuya, Wilson Massamitu; Sartori, Maria Marcia Pereira [UNESP]; Pezzato, Luiz Edivaldo [UNESP]; Barros, Margarida Maria [UNESP] (Revista Brasileira Zootecnia Brazilian Journal Animal Sci, 2022)
The effects of dietary digestible protein (DP) levels (22, 26, 29, 32, and 34%) and different stressors (cold-induced stress, CIS; heat/dissolved oxygen-induced stress, HDOIS; transport-induced stress, TIS; and size-sorting-induced stress, SSIS) on hemato-biochemical parameters were evaluated. Four hundred and forty Nile tilapia fingerlings were distributed into 40-250 L aquaria and fed experimental diets for 110 days, and fed each of the five experimental diets, that were randomly distributed to eight replicates per treatment. Then, different groups of fish were subjected to one type of stress. Groups of 40 fish were used on CIS (17 degrees C), HDOIS (32 degrees C), and TIS (4 h), and a group of 140 fish on SSIS (15 min air exposure and 60 s handling). There was no effect on hemato-biochemical profile when DP levels were compared, neither before nor after stress; however, there was a significant stress effect. Digestible protein did not mitigate stress response under SSIS and CIS; lymphopenia and neutrophilia were the main cell-mediated immune response; dietary 22 and 26% DP impaired oxygenation on SSIS and TIS; fish under HDOIS and SSIS demanded more energy using triglycerides as an energy source; the diet formulated to contain 22% DP was not adequate to keep homeostasis under temperature stress. Cluster analysis showed that, for DP levels below the requirement for growth, SSIS and CIS were considered the most stressful conditions. At 34% DP level, HDOIS response was comparable to that of non-stressing conditions.
Keywords: Cluster analysis; Fish health; Oreochromis niloticus; Physiological response; Stressors